Spontaneous resolution of keratoacanthoma centrifugum marginatum. (October 2014) - El‐Khayat, R. H.; McGrath, C.; Walsh, M. Y.; Ferguson, M.; Hoey, S. E.
Summary Keratoacantnoma centrifugum marginatum (KCM) is a rare variant of keratoacantnoma, with > 40 cases reported world wide. Spontaneous resolution of KCM is very rare. To our knowledge, this is the first case of KCM with spontaneous resolution as documented by serial photographs.